Use of antitussive medications in acute cough in young children. Issue 3 (18th June 2021) - Lam, Samuel H. F.; Homme, James; Avarello, Jahn; Heins, Alan; Pauze, Denis; Mace, Sharon; Dietrich, Ann; Stoner, Michael; Chumpitazi, Corrie E.; Saidinejad, Mohsen
Abstract: Acute cough, a common complaint in young children, is often the result of a viral upper respiratory infection. Cough and cold remedies generate billions of dollars in annual sales in the United States, despite a lack of evidence of their efficacy and multiple warnings by the US Food and Drug Administration. The current article begins with the best available evidence for common over‐the‐counter (OTC) and prescription antitussive remedies in children. The article concludes with a discussion of the pros and cons for the use of antitussives in children with cough. In general, OTC antitussive medications should not be routinely used in children under 2 years of age. In certain cases, antitussives with minimal adverse profile and some evidence of benefit may be recommended after informed counseling.